Pengaruh Budaya Organisasi Terhadap Kinerja Pegawai Dinas Kependudukan Dan Pecatatan Sipil Kabupaten Wajo - Nizar, Muh; Muhammadiyah, Muhammadiyah; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2021)
This study purposed to find out and analyze how big the influence organization culture on the performance of employees of the Department of Population and Civil Registration of Wajo Regency. This study used quantitative. Data collection techniques were observation and questionnaire related to research variables. The population in this study were 48 employees at population and Civil Registry Office, Wajo Regency. Sampling in this study used saturated sampling or taking all members of the population used as samples, with a total sample of 48 people. The results of this study showed that organizational culture influenced employee performance at the Office of Population and Civil Registration Wajo Regency, as indicated by the magnitude of the coefficient of determination or R Square (R2) of 0.267% meant that the organizational culture variable had an influence of 26.7% on employee performance variables Wajo Regency's Population and Civil Registry Office.